Using PROMIS-29 to determine symptom burdens in the context of the Type 1 and 2 systemic lupus erythematosus (SLE) model: a cross sectional study - Kai Sun; Amanda M. Eudy; Nathaniel Harris; David S. Pisetsky; Lisa G. Criscione-Schreiber; Rebecca E. Sadun; Jayanth Doss; Megan E. B. Clowse; Jennifer L. Rogers (SpringerOpen, 2023)
Abstract Objective To account for heterogeneity in systemic lupus erythematosus (SLE) and bridge discrepancies between patient- and physician-perceived SLE activity, we developed the Type 1 and 2 SLE model. We examined PROMIS-29 scores, a composite patient-reported outcome (PRO) measure, through the lens of the model. Methods Patients completed PROMIS-29 and the polysymptomatic distress scale (PSD). Rheumatologists completed the SLE disease activity index (SLEDAI), and physician's global assessments (PGAs) for Type 1 and 2 SLE. We defined Type 1 SLE using SLEDAI, Type 1 PGA, and active nephritis, and Type 2 SLE using PSD and Type 2 PGA. We compared PROMIS-29 T-scores among Type 1 and 2 SLE groups and explored whether PROMIS-29 can predict Type 1 and 2 SLE activity. Results Compared to the general population, patients with isolated Type 1 SLE reported greater pain and physical dysfunction but less depression and improved social functions; patients with high Type 2 SLE (irrespective of Type 1 activity) reported high levels of pain, fatigue, and social and physical limitations. Patients with minimal Type 1 and 2 SLE had less depression and greater physical functioning with other domains similar to national norms. PROMIS-29 predicted Type 2 but not Type 1 SLE activity. Conclusion PROMIS-29 similarities in patients with high Type 2 SLE, with and without active Type 1 SLE, demonstrate the challenges of using PROs to assess SLE inflammation. In conjunction with the Type 1 and 2 SLE model, however, PROMIS-29 identified distinct symptom patterns, suggesting that the model may help clinicians interpret PROs.